I just forgot - Mayer, Mercer, 1943- (New York : Golden Books, 1988)
Sometimes Little Critter remembers things, and sometimes he just forgets.
"Mercer Mayer's Little Critter"--Cover p. [4].
2.7
K-3
K-3
490
Keywords: Little Critter (Fictitious character) -- Fiction; Memory -- Fiction; Humorous stories; Little Critter (Fictional character) -- Fiction; Memory -- Fiction; Humorous fiction